Effect of Fruit and Vegetable Intake on Oxidative Stress and Dyslipidemia Markers in Human and Animal Models - Domínguez-Avila, Jesús Abraham; Alvarez-Parrilla, Emilio; Rosa-Carrillo, Laura A. de la; Martínez-Martínez, Alejandro; González-Aguilar, Gustavo A.; Gómez-García, Consuelo; Robles-Sánchez, Maribel (IntechOpen, 2011)
None